Locating surface cracks and static objects on 2D structures using NDT scanning techniques - Cheang, Clarence Jing Loong (2017)
Structural health monitoring (SHM) techniques are crucial for the maintenance of civil, aerospace and mechanical industry. Early detection of ailments such as fatigue, crack and creep aids in prevention of structural integrity failure and thus, enhances safety and well-being of its occupants. However, existing techniques in SHM can be further improved for efficient detection of ailments if integrated together. There are several SHM techniques and many new ones are emerging fast thus in this FYP, existing techniques such as Lamb waves propagation and electro-mechanical impedance (EMI) techniques are explored separately and collectively. In this project, Lamb waves propagation method was carried out on 1-D and 2-D structures, which were subjected to variations of loading magnitudes and locations, by changing input Lamb waves frequencies. Piezoelectric actuators and sensors were used to propagate waves on the host structure. EMI was used to find out suitable frequency of input Lamb waves for determining the discontinuity in the structure as well as when combined with the Lamb waves, resulted in complementary nature which were very effective in load detection. Furthermore, this project also presents statistical indicators in the form of transient energy to relate the load/damage severity with varying loads and distance between sensors and actuators. It also explored air - surface and air -air properties of Lamb waves propagation and relationships between the loading condition and output signals using transient energy indicator.